Phenotypic Diversity of MV1 Generation Mutants of Terigas Orange Induced by Gamma-Ray Irradiation - Noor Farid; Agus Sarjito; Zulfa Ulinnuha; Marya Ulfa (Agrotechnology Research Journal, 2025)
Terigas orange is a nationally superior variety from Sambas, West Kalimantan, but its fruit quality remains less competitive than imported varieties, which are typically brightly colored and seedless. Genetic improvement through gamma-ray irradiation was applied to enhance its traits. This study aimed to evaluate the effects of 6 kRad gamma-ray irradiation on the morphological and fruit characteristics of Terigas orange mutants. Conducted from May to July 2023 at the Screenhouse, Faculty of Agriculture, Jenderal Soedirman University. The experiment used a Randomized Block Design. The data were analyzed using Least Significant Difference and the Least Significant Increase. A test at the 5% level is used to compare the diversity of mutants with normals. Results showed significant variations in plant height, stem diameter, leaf width, and petiole length. Qualitative changes were observed in leaf shape, margin, base, type, color (upper and lower surfaces), and length. Mutant fruits exhibited stronger aroma, higher brix levels, a sweeter yet slightly sour taste, and more seeds compared to the normal.